Taxonomic studies on Mucor inaequisporus, isolated for the first time in South America - Santiago, Andre Luiz C. M. de A.; Rodrigues, Andre [UNESP]; Canedo, Enzo M.; Filho, Edson R. (Mycotaxon Ltd, 2013)
Mucor inaequisporus (Mucorales, Mucoromycotina) was isolated from Syzygium cumini, a common introduced tree species in Brazil. It is distinguished from similar species by producing straight or undulate sporangiophores with randomly distributed irregular swellings. The columellae are mostly pyriform at 25 degrees C, but oblong, conic, ellipsoid, and obovoid columellae were also found. The sporangiospores vary in size and shape, with a minor proportion exhibiting an irregular shape. ITS- based phylogenetic analyses reveal that M. inaequisporus is closely related to M. amphibiorum and M. nederlandicus. This species can grow between 20 and 30 degrees C with optimal development at 25 C, but variations in the shape of sporangiospores and columellae caused by incubation under different temperatures were observed. No growth was detected at 10 and 40 degrees C.
Keywords: DNA sequencing; growth rate; zygomycete